Study of human error from incident investigation in upstream facilities - Abd Halim, Abdul Hafiz; Mohd Ghazi, Tinia Idaty; Mohd Yassin, Faizah; Mohd Tohir, Mohd Zahirasri (John Wiley & Sons, 2024)
Human failures are a major cause of breakdowns in upstream facilities because of challenging working conditions. A study of human errors from an incident investigation in upstream facilities was carried out to understand the topography of human errors. A Tripod Beta diagram was developed from 107 incidents gathered during 2017–2020, and the human error taxonomy was used to identify the human errors caused by individuals and contributory human factors responsible for the incidents. A mistake is the most common human failing in a major incident, contributing to 59%, followed by a violation and a skill‐based error with scores of 36% and 5%, respectively. Knowledge‐based mistakes were prevalent in 48% of the analyzed reports, indicating a significant gap in any decision involving problem‐solving and diagnosis. Situational and routine violations with 14% and 10% scoring, respectively, show the complexity of the offshore work environment, which prompts workers to violate and believe that jobs cannot be completed without violations. Disciplinary action, providing a safer workplace, and enhancing the safety culture were proposed to combat workplace violations. Meanwhile, an up‐skilling of the workforce with adequate information and instruction will mitigate human errors leading to a mistake. Lastly, revisiting human factor engineering is required to prevent slip and lapse errors.